Computerized Working Memory Training in Remission From Major Depressive Disorder: Effects on Emotional Working Memory, Processing Speed, Executive Functions, and Associations With Symptoms - Ronold, Eivind Haga; Joormann, Jutta; Hammar, Åsa (Frontiers in Behavioral Neuroscience, 2022)
Introduction: Remission from Major Depressive Disorder (MDD) is associated with residual symptoms related to reduced functioning, quality of life and relapse risk. Previous studies have raised questions about mechanisms involved in- and affected by cognitive training. The current study investigated the associations and changes among depressive symptoms, rumination, Processing Speed (PS), Executive functioning (EF), and emotional working memory (e-WM) pre- post Computerized Working Memory Training (CWMT). Method: Twenty-nine remitted participants were included in a pre- post pilot study of within subject effects of online CWMT. Twenty participants completed the intervention and pre- post-tests of EF and PS, e-WM, in addition to symptom- and rumination measures. Associations between- and changes in symptoms and cognition were investigated pre- post. Associations between improvements in CWMT, depression history, and changes in cognition were explored. Hypotheses and statistics were preregistered before data was analysed. Results: Manipulation of negatively valanced stimuli in e-WM showed an inverse association with rumination pre intervention, but the association disappeared following intervention. Cognitive functioning improved in most conditions with largest effects in EF. Symptoms did not change in the remitted sample. CWMT improvements were related to improvements in some aspects of EF and PS, but also to worse self-reported attention. Depression history was related to less improvement in EF. Limitations: Samples size was small and there was drop out from the study. There was no control group, thus precluding practice- and placebo effects and causal relationships.